The Leukotriene B-4/BLT1 Axis Is a Key Determinant in Susceptibility and Resistance to Histoplasmosis - Secatto, Adriana; Soares, Elyara Maria; Locachevic, Gisele Aparecida; Assis, Patricia Aparecida; Garcia Paula-Silva, Francisco Wanderlei; Serezani, Carlos Henrique; Medeiros, Alexandra Ivo de [UNESP]; Faccioli, Lucia Helena (Public Library Science, 2014)
The bioactive lipid mediator leukotriene B-4 (LTB4) greatly enhances phagocyte antimicrobial functions against a myriad of pathogens. In murine histoplasmosis, inhibition of the LT-generating enzyme 5-lypoxigenase (5-LO) increases the susceptibility of the host to infection. In this study, we investigated whether murine resistance or susceptibility to Histoplasma capsulatum infection is associated with leukotriene production and an enhancement of in vivo and/or in vitro antimicrobial effector function. We show that susceptible C57BL/6 mice exhibit a higher fungal burden in the lung and spleen, increased mortality, lower expression levels of 5-LO and leukotriene B-4 receptor 1 (BLT1) and decreased LTB4 production compared to the resistant 129/Sv mice. Moreover, we demonstrate that endogenous and exogenous LTs are required for the optimal phagocytosis of H. capsulatum by macrophages from both murine strains, although C57BL/6 macrophages are more sensitive to the effects of LTB4 than 129/Sv macrophages. Therefore, our results provide novel evidence that LTB4 production and BLT1 signaling are required for a histoplasmosis-resistant phenotype.